PERMAINAN GOBAK SODOR DAN PEMBENTUKAN KARAKTER DALAM PENDIDIKAN JASMANI BAGI PESERTA DIDIK TBSM - Subagio, Rohmad; Muhyidin, Asep; Mukti Leksono, Suroso; Jamaludin, Ujang (JIPIS, 2024)
Traditional sports games are increasingly being marginalized by the presence of modern games such as Play Station and online games. Online games are generally played statically, which causes children to become indifferent to the environment, thus affecting children's social interactions. The impact is that children develop into shy, solitary and individualistic individuals. Physical education is an important part of the education given to students at school. The expected goal is to help students acquire the skills and physical fitness needed to live a healthy and active life. By implementing the traditional game gobak sodor, it is hoped that students will easily participate in physical education learning which includes character education, and students' skills and activeness will be further developed so as to make learning centered on students. This journal was written based on a literature study to explain that traditional games can not only encourage students to engage in social interaction between friends, but in accordance with the title above, the character of students in physical education can also be formed through traditional games. For this reason, traditional games have a very important role in forming students' characters such as independence, creativity and working together, because this behavior has become an achievement in the world of education and preserving Indonesian culture. Keywords: Gobak Sodor game, character, physical education